The women's liberation movement in transnational perspective: the US, UK, and France, 1967-79 - Little, T (2020)
Most histories of the women’s liberation movement (WLM) are nationally focused. Yet they contain glimpses of the transnational, from assertions that the American movement sparked European activity, to accounts of theory, protest tactics, and organisational ideas criss-crossing national borders throughout the movement. Transnational WLM histories have recently emerged, but they usually focus upon specific transfers. Even when taken together it is difficult to see what they tell us more broadly about how the movement operated across borders. To explore this topic, this thesis analyses links between the US, UK, and France. This provides a triangular case study, allowing the analysis of crosscurrents, multiple pathways, and entangled links.